Support for mobilising medical students to join the COVID-19 pandemic emergency healthcare workforce: a cross-sectional questionnaire survey - Sten Rasmussen; Mike Sæderup Astorp; Gustav Valentin Blichfeldt Sørensen; Jeppe Emmersen; Alexander Wolfhagen Erbs; Stig Andersen (BMJ Open)
Objective To identify what motivates medical students to join a pandemic emergency healthcare workforce.Design Cross-sectional study.Setting Aalborg University, Denmark.Participants All medical students.Main outcome measures Motivational points as perceived by the students to be important. Demographic characteristics and 11 motivational domains scored on a Visual Analog Scale from 0 (low) to 100 (high) responding to the question: ‘To what degree are the following statements important for you to join a national emergency preparedness workforce?’ The questionnaire was developed by an expert panel in a process of four iterations.Results A total of 486 students of 688 (70.6%) completed the survey within 7 days in March 2020. 80% had decided to join the pandemic emergency healthcare workforce. Ranked median scores for motivational statements in each domain were: care, 100; learn, 90; pride, 83; team, 77; needed, 75; safety, 75; supervision, 75; job, 73; duty, 66; salary, 62; historic, 50. Supervision (p<0.001), salary (p<0.001) and duty (p=0.001) were given increasing priority with advancing study years. Interestingly, students added that support by the university and clarification of study plans were priorities.Conclusions Results guide decision-makers and colleagues on how to motivate or reinforce medical students in joining the pandemic emergency healthcare workforce. Importantly, students emphasised protection for themselves.